The Sociological Imagination in Challenging Times - Nathan S. Palmer (Journal of Public and Professional Sociology)
This critical essay argues the events of the last few years have made sociology more relevant to students’ lives and increased their need for and the utility of a well-developed sociological imagination. To meet the opportunities created by this moment, sociology educators need well-designed and highly effective pedagogical interventions that develop their students' sociological imaginations. Unfortunately, much of the available scholarship on developing students' sociological imaginations lacks the conceptual clarity and empirical rigor needed to discern which pedagogical interventions are most effective. After a detailed review of the scholarly problems surrounding the sociological imagination, recommendations for expanding the field are provided.